1994
DOI: 10.1099/0022-1317-75-12-3547
|View full text |Cite
|
Sign up to set email alerts
|

Papaya ringspot potyvirus: isolate variability and the origin of PRSV type P (Australia)

Abstract: We have sequenced the coat protein gene of nine isolates of papaya ringspot virus (PRSV) including six Australian and three Asian isolates and compared these with four previously reported sequences of PRSV. There was up to 12 % sequence variation between isolates at the nucleotide level. However, there was no significant difference between the sequences obtained from Australian isolates irrespective of whether they were PRSV type P (cucurbit or papaya infecting) or PRSV type W (cucurbit infecting) and these is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 28 publications
1
64
0
7
Order By: Relevance
“…The grouping of Indian isolates with American isolates (Brazil, Mexico, and Hawaii) and the level of divergence seen in the CP gene among the Indian isolates (Jain et al 1998;Bag et al 2007) certainly implicate the Indian subcontinent in the spread of PRSV to these countries. Close sequence similarity between the P and W biotypes of PRSV from the same geographic region suggests that they may have evolved by mutations (Bateson et al 1994). The sequence similarity matrix generated from whole genome sequences of PRSV isolates reported from different geographic locations and their individual genetic components revealed that all the cistrons follow the divergence exhibited by the whole genome, except P1, which is much more variable than the full genome (Inoue-Nagata et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The grouping of Indian isolates with American isolates (Brazil, Mexico, and Hawaii) and the level of divergence seen in the CP gene among the Indian isolates (Jain et al 1998;Bag et al 2007) certainly implicate the Indian subcontinent in the spread of PRSV to these countries. Close sequence similarity between the P and W biotypes of PRSV from the same geographic region suggests that they may have evolved by mutations (Bateson et al 1994). The sequence similarity matrix generated from whole genome sequences of PRSV isolates reported from different geographic locations and their individual genetic components revealed that all the cistrons follow the divergence exhibited by the whole genome, except P1, which is much more variable than the full genome (Inoue-Nagata et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The cp gene of PRSV could be divided in three regions, N terminus (first 224 nucleotides), C terminus (last 59 nucleotides, including the stop codon), and core (641 nucleotides between the N and the C terminus), as suggested for other potyvirus (Shukla & Ward, 1989;Bateson et al, 1994). The analysis of the divergence between PRSV HA 5-1 and the Brazilian isolate throughout these three regions revealed that divergence is concentrated in the N terminus (21 nucleotides different) and core (36 nucleotides different) regions; nucleotide differences were not seen in the C terminus region.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence diversity of the isolates in the country as well as the surrounding countries would need to be known. The coat protein genes of many PRSV isolates in the world have been sequenced (e.g., BATESON et al 1994;WANG and YEH 1997). 9 Final Comments: an Interface Between "Innate" and "Acquired" Immunity…”
Section: Implementation Of Transgenic Papaya Throughout the Worldmentioning
confidence: 99%